Studi In Silico Senyawa Aktif Rimpang Kunyit (Curcuma Domestica) terhadap Penghambatan Acetylcholinesterase, Microtubulin (Beta Tubulin), dan Aktivasi Calcium Channel sebagai Terapi Antelmintik - Avicenna Shafhan Arfi; Rosaria Dian Lestari; Dini Sri Damayanti (Jurnal Kedokteran Komunitas, 2020)
Background: Helminthiasis are a pandemic and has a high prevalence in Indonesia. Turmeric rhizome contains curcuminoids and essential oils as its active compounds. However, their mechanism as an anthelmintic is unknown. Therefore, further research is needed to find out the exact mechanism of turmeric rhizome as an anthelmintic.Method: The effectivity of turmeric rhizome’s active compounds against Acetylcholinesterase, Microtubulin (Beta Tubulin), and Calcium Channel was evaluated by Docking Server with Pirantel Pamoat, Mebendazole, and Praziquantel as sequential control.Results: Curcumin Sulfate was identified as having a low affinity for Acetylcholinesterase with -5,62 kcal/mol free bond energy. Cyclocurcmin has a high affinity for Beta Tubulin and Calcium Channel with -7,39 and -8,36 kcal/mol free bond energy sequentially. Meanwhile Dihydrocurcumin and Curcumin Sulfate have a high affinity for Calcium Channel with -7,19 and -7,41 kcal/mol free bond energy sequentially.Conclusion: The active compound of turmeric rhizome has a low affinity for the inhibition of Acetylcholinesterase in Ascaris lumbricoides. Cyclocurcumin has a high affinity for the inhibition of Microtubulin (Beta Tubulin) and Calcium Channel in Ascaris lumbricoides. Meanwhile Dihydrocurcumin and Curcumin Sulfate have a high affinity for the activation of Calcium Channel in Schistosoma sp.Keywords: Anthelmintic, Turmeric Rhizome, In silico